The Islamic studies education curriculum of Malaysian national schools: a study of its philosophy and content - Hashim, Rosnani (Routledge, 2018)
Islamic Studies Education (ISE) or Islamic Religious Education (IRE) is vital in Muslim education. It is through this subject that the Islamic tradition, values and practices are transmitted to the next generation. There are several providers of ISE in Malaysia namely the traditional pondok and madrasah, the Sekolah Agama Rakyat (SAR) and the Assisted Sekolah Agama Rakyat (SABK), the Sekolah Menengah Kebangsaan Agama (SMKA), the Sekolah Berasrama Penuh Integrasi (SBPI) and the national school system. This chapter focuses on the National Primary and Secondayy schools which is the main player, with the largest number of students enrolled. It examines and evaluates the curriculum applied in the system in four aspects – philosophy, content and scope, teaching methodology and assessment. Several shortcomings were identified for both primary and secondary schools. The goals and objectives of both levels are found to be similar and do not distinguish the students based on their stages of human development. The content too has several shortcomings such as being overwhelmed with adab but lacks character building with the Prophet as the exemplar, lack of hadith and stories of the prophets in the Qur’an, and lack of globalization- related topics. The methods use were found not to sync with the needs of the era. The chapter ends with suggestions for the improvement of ISE.